Manajemen Pelayanan Publik dalam Pelaksanaan Manasik Haji untuk Calon Jamaah Umroh di KBIHU Armina Kota Medan - Saidi, Saidi; Khoiri, Nisful (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
After the creed, prayer, zakat, and fasting, the fifth pillar of Islam is haji. Every Muslim who meets the material, physical, and scientific requirements by visiting Baitullah and performing a number of activities related to Hajj, such as conditions, pillars, obligatory, and sunnah Hajj, is obligated to make the pilgrimage. because the pilgrimage is unlike other forms of worship, which must be carried out at a specific time and location. In order to avoid any issues, the Hajj services must be carried out flawlessly and professionally. This includes the crucial role played by the Hajj Guidance Group (KBIH). This article was written using a qualitative method. While field research is the method of choice, The study reveals that the program for carrying out the Hajj at KBIHU Armina, MedanCity, aims to increase pilgrimage knowledge, beginning with registration, providing guidance on the Hajj rituals, assisting with the carrying out of the pilgrimage in Saudi Arabia, returning, and ending with coaching and guidance following the carrying out of the Hajj. The utilization of strategies in Hajj and Umrah direction through Hajj ceremonies can be of more than one kind (changes) while executing the Hajj customs with an end goal to build information on the journey for planned travelers at KBIHU Armina, MedanCity. Forthcoming pioneers can be roused in different ways. A strategy's viability and pertinence to the boss' material should be considered while choosing and applying it. The talk technique, the reproduction strategy, and the Q & A strategy are undeniably used in the Hajj ceremonies.